Analisa Stabilitas Dinding Penahan Tanah Ruas Jalan Kambelu-Nasiri Kecamatan Huamual Kabupaten Seram Bagian Barat - Talaud, Aprilia Agnes; Maitimu, Anthoneta; Latar, Sjafrudin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Kambelu Hamlet-Nasiri Hamlet road section is a road section that connects several hamlets in Huamual Balik District, West Seram Regency. Functional length 1200m ( STA 00+000 – 01+200) and paving width 4m. This road section often occurs landslides on the slopes around the road section, especially at STA 00+300, STA 00+350, STA 00+400. There was one point that experienced a severe landslide at STA 00+400. This study is to analyze the appropriate soil retaining wall on the Kmbelu - Nasiri road, Huamual Balik District, West Seram Regency.The methods (SNI) for moisture content testing (SNI 1965:2008), content weight testing (SNI 03-3637-1994), specific gravity testing (SNI 1964:2008), filter analysis testing (SNI ASTM C136:2012), atterberg limit testing (SNI 1967:2008) and soil compaction testing (SNI 1742:2008). The methods used are the Rankine method and the Terzhagi method. The distribution of active and passive lateral soil pressure is active soil pressure (Pa) = 75.751 active soil moment = 151.50 kN/ passive soil pressure = 21.042 kN/ passive soil moment = 7.007 kN/ The design of the soil retaining wall is a cantilever type with dimensions, H = 6 m, B = 4 m. The planned type and dimensions have been adjusted to the dimensions of the landslide on the Kambelu - Nasiri STA 00 + 400 road section. And the results of stability to shear force = 2.621 ≥ 2.0 (safe), stability to rolling force ≥ 2.0 (safe) and stability to ground carrying capacity Qult = 868.333 > 108.488 are said to be safe because the maximum Q value is no more than the Qult value.